Tunariorthis, a New Substitute Name for Tunaria Benedetto, 2013 (Brachiopoda, Heterorthidae) - Benedetto, Juan Luis Arnaldo (2014)
THE generic name Tunaria was erected by Benedetto (2013) to include the species Orthis berthoisi? var. erratica Davidson, 1869, from England, France and Spain, and the new species Tunaria cocksi Benedetto, 2013, from the Late Ordovician San Benito Formation of Bolivia. According to the ICZN (1999, Art. 53, 60) Tunaria Benedetto, 2013, must be rejected and replaced with a new name because it is a junior synonym of the linguloidean brachiopod Tunaria von Hoek, 1912, p. 247 (type species Tunaria cochabambina), non Link, 1807, which was renamed as Tunarites by Cooper and Muir-Wood (1951). The name Tunaria was used subsequently by Pirán (1957) to designate an acanthosomatid hemiptera from Bolivia (type species Tunaria andicola Pirán 1957) which is also a junior synonym of the cnidarian Tunaria Link 1807. Therefore, the new name Tunariorthis nom. nov is proposed to substitute the illegitimate name Tunaria.